Table S1, Composite depths and age models for ODP coring sites 964 and 967 - Felix J Elling; Jordon D Hemingway; Jenan Kharbush; Kevin W Becker; Catherine Ann Polik; Ann Pearson (PANGAEA, 2021)
This dataset contains composite depths and age models for ODP sites 964 and 967, including: event name, sapropel layer, sample ID, site, hole, core, section, section position, depth (raw), depth (composite, revised), age, comment, and reference. All data were compiled from the literature. This work was supported by the Gordon and Betty Moore Foundation.
In: Elling, FJ et al. (2021): Mediterranean sapropel bulk organic matter and biomarker concentrations and carbon isotope compositions [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937082